(untitled) (Texas Journal of Medical Science, 2022)
A cross-sectional study was conducted at different hospitals in Iraq to find out health outcomes in patients with rheumatoid arthritis in pregnant women In this study, 170 patients were collected and divided into two groups (90 patients diagnosed with pregnancy and rheumatoid arthritis) (observing 80 patients diagnosed with pregnancy and without rheumatoid arthritis or mild activity to the disease) with a period from 1 Nov 2019 to Aug 2020 Rheumatoid arthritis (RA) is a type of arthritis that mainly affects the joints, which means that the immune system does not work as well as it should, causing inflammation in the joints. Symptoms may include swelling, stiffness, discomfort, and pain and may cause restricted movement The statistical analysis program IBM SPSS SOFT 25.0 was used, where the statistical values and relationships between the patient group and the disease activity were presented, in addition to Evaluate the final outcomes for the patients of this study in terms of complications and antepartum outcomes, Intrapartum outcomes, and Postpartum outcomes